Need of elevating the role of shariah board and portraying them significantly on Islamic bank websites: Why and how? / Tahreem Noor Khan. - Noor Khan, Tahreem Noor Khan (Universiti Teknologi MARA Selangor, 2018)
Islamic banking emerged rapidly to fulfil the financial needs of Muslim consumers, by using different viable modes of Islamic financing. These tools of financing were designed to avoid risk-free return, unjustified increase of money on money and uncertainty. To make these tool authentic, in all Islamic bank, Shariah board members are the pillar of the management structure. The presence of renowned scholars in a bank actually helps to increase the worth of a Shariah financial brand as they are the one who oversee and supervise the activities of banks. However, it is noticed that confusion and misperception exist generally about Islamic banks due to lack of devising authentic products, modes of structure and operational default. To identify the customer perception about Shariah scholars, Online Survey was conducted. In total 92 respondents participated. With that, 14 top Islamic bank websites (Bahrain, Lebanon, Nigeria, Saudi Arabia, Srilanka, Indonesia, Bangladesh, UAE, Pakistan, Malaysia, Kuwait, Jordan, Eygpt, Oman) was observed to figure how they have given importance and exposure to the Shariah board members. The findings suggested that web-marketing could highlight the role of Shariah scholars so that both users and non-users of Islamic banks were able to learn more about the machinery of Islamic financial products. In addition, Shariah board scholars should consciously reconsider and review their past and present approaches so as to perform better in the future.